Effects of adverse life events on heart rate variability, cortisol, and C‐reactive protein. (16th May 2014) - van Ockenburg, S. L.; Tak, L. M.; Bakker, S. J. L.; Gans, R. O. B.; de Jonge, P.; Rosmalen, J. G. M.
<x xml:space="preserve">Abstract</x> Objective Our objective was to assess whether self‐reported adverse life events during childhood or over the lifespan are associated with altered activity of the autonomic nervous system (ANS), the hypothalamic‐pituitary‐adrenal axis (HPA axis), and the immune system. Method This study was performed in a population‐based cohort of 1094 adults aged 33–79 years, 46.3% male, average age 53 (SD 11.4). Two waves of data were collected at a 2‐year interval, enabling replication of the analyses. Cumulative exposure to adverse life events was assessed by means of the List of Threatening Experiences. ANS function was assessed by spectral analysis of heart rate variability in the high‐frequency band (HRV‐HF). HPA axis function was assessed by 24‐h urinary free cortisol (24‐h UFC) excretion. Inflammation was assessed by high‐sensitive C‐reactive protein (hsCRP). Results Multiple linear regression analyses did not reveal any significant associations, with the exception of one significant negative association between the lifetime score of adverse life events and HRV‐HF β = −0.028; P = 0.037 at baseline, but not at follow up 2 years later. Conclusion In a large population‐based cohort, adverse life events were not consistently associated with HRV‐HF, 24‐h UFC or (hsCRP).